Effect of ultraviolet absorption reagent for determination of piperidinium ionic liquid cations by ion pair chromatography with indirect ultraviolet detection. Issue 13 (9th August 2017) - Zhang, Xin-xin; Yu, Hong; Wang, Gang
ABSTRACT: Indirect ultraviolet detection method is a simple and effective method for the determination of ionic liquid cations without ultraviolet absorption group. This paper focused on the influence of different background ultraviolet absorption reagents on the determination of piperidinium ionic liquid cations by ion pair chromatography with indirect ultraviolet detection. Ultraviolet absorption reagents are divided into cationic (4-aminophenol hydrochloride, 1-ethyl-3-methylimidazolium tetrafluoroborate, and N -ethylpyridinium tetrafluoroborate), anionic (potassium biphthalate and 5-sulfosalicylic acid), and amphiprotic ( p -aminobenzoic acid). The results showed that piperidinium cations can be separated and detected by cationic and anionic ultraviolet absorption reagents. In general, the cationic ultraviolet absorption reagents have the best effect for separation and detection of the piperidinium cations by ion pair chromatography with indirect ultraviolet detection. GRAPHICAL ABSTRACT: